2014
DOI: 10.1097/mpg.0b013e31829e25b8
|View full text |Cite
|
Sign up to set email alerts
|

Biliary Atresia in Children With Aberrations Involving Chromosome 11q

Abstract: F umarate hydratase (FH) or fumarase deficiency (FD) is an extremely rare (Online Mendelian Inheritance in Man no. 606812) inherited metabolic disease with the majority of infants presenting with growth failure, developmental delay, and severe neurological involvement. FH is an essential enzyme of the tricarboxylic cycle and exists in 2 isoforms: mitochondrial (nuclear encoded), which catalyses the reversible hydratation of fumarate to malate, and cytosolic, which metabolises fumarate released by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…The etiology of BA is unknown, although epidemiological studies support an infection or toxin exposure, likely occurring prenatally, in the setting of genetic susceptibility . Our group recently identified an isoflavonoid called biliatresone that has been implicated in outbreaks of a BA‐like syndrome in Australian livestock and also causes selective EHBD destruction in zebrafish .…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of BA is unknown, although epidemiological studies support an infection or toxin exposure, likely occurring prenatally, in the setting of genetic susceptibility . Our group recently identified an isoflavonoid called biliatresone that has been implicated in outbreaks of a BA‐like syndrome in Australian livestock and also causes selective EHBD destruction in zebrafish .…”
Section: Discussionmentioning
confidence: 99%
“…3 Division of Pediatric Gastroenterology, Hepatology, and Nutrition, The Children's Hospital of Philadelphia, Philadelphia, PA 19104, USA. 4 Sackler Faculty of Medicine, Tel-Aviv University, Tel-Aviv, Israel. 5 Wellcome Trust Sanger Institute, Wellcome Trust Genome Campus, Hinxton, Cambridge CB10 1SA, UK.…”
Section: Isolation and Biochemical Characterization Of Biliatresonementioning
confidence: 99%
“…Neither form of BA displays Mendelian inheritance, and most twin studies have shown nonconcordance, thus arguing against a single genetic determinant. Genome-wide association studies (GWAS) have led to identification of potential BA susceptibility loci on several different chromosomes, and a recent study suggested an association between BA risk and specific mitochondrial DNA haplogroups (3)(4)(5)(6). Unfortunately, none of the affected genes within these regions have been identified.…”
Section: Introductionmentioning
confidence: 99%